Considerations on the development of the stem apex to decide when to fertilize wheat in the Semiarid Pampas Region (I) (Semiárida, 2020)
The development of the culm apex was considered in order to apply nitrogen fertilizer. The trial was carried out with Pima 77, Las Rosas INTA and Marcos Juarez INTA fertilizing to 5, 12 and 22 cm of the apex height. It has not been observed interaction between cultivar sand application moment Pima and Las Rosas INTA overcame significantly Marcos Juarez INTA's yield with a production of 1887,1976 and 1316 kg/ha respectively. About the application moment has not been recorded significant differences among cultivar' s yield although the production increased as nitrogen was applied to plants with culm apex 5 cm height. Water consumption resulted equivalent throughout the fertilization moments studied without significant correlation between grain yield and water consumption (r= 0,23).